2016
DOI: 10.21162/pakjas/16.4781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Fat on Dry Matter Intake, Nutrient Digestibility, Milk Yield and Milk Composition of Ruminants

Abstract: Use of supplemental fat in the ration of ruminants is increasing. This review provides the recent knowledge on the effect of supplemental fat in ruminants' diets. In addition, the effect of supplemental fat on the nutrient intake, nutrient digestibility and body weight gain are also discussed. Research conducted on dairy cows shows that extra fat addition decreases dry matter intake (DMI) with the negative effect on digestibility. Gut peptides released in response to extra fat which have negative effect on DMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
3
1
1
Order By: Relevance
“…The findings of the current study were in line with those of other studies in which it was reported that supplementation of ruminally protected fat at higher levels than 2.5% reduced the DMI (Marinova et al, 2001;Haddad & Younis, 2004). The gut peptides released in response to higher fat levels had a negative impact on DMI (Nawaz & Ali, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The findings of the current study were in line with those of other studies in which it was reported that supplementation of ruminally protected fat at higher levels than 2.5% reduced the DMI (Marinova et al, 2001;Haddad & Younis, 2004). The gut peptides released in response to higher fat levels had a negative impact on DMI (Nawaz & Ali, 2016).…”
Section: Resultssupporting
confidence: 92%
“…In fact, when grazing cattle were offered concentrate supplement, they showed 0.9 kg/d higher total dry matter intake [45], similar to buffaloes fed with Diet B in this study. However, the improved feed intake by buffaloes fed with Diet C in this study disagreed with other studies that concluded that supplementation of rumen bypass fat at levels higher than 2.5% could reduce the DMI [46,47] due to the release of peptides in the gut as a response to a higher fat diet composition [48]. Furthermore, the addition of long-chain fatty acid capsulated with Ca salts at a high level was capable of depressing animal daily intake [49].…”
Section: Discussioncontrasting
confidence: 96%
“…This supports the findings of our study, in which milk fat depression (MFD) was obtained as a result of corn oil supplementation accompanied by a non-significant reduction in milk production compared to the control. The similar effect on protein and lactose percentages in our results was supported by previous research by other authors, which resulted in unaffected protein and lactose percentages when edible oils were supplemented [ 23 , 26 ]. This could be related to decreased fiber digestion and feed degradability when corn oil is supplemented with the dairy goat diet [ 27 ].…”
Section: Discussionsupporting
confidence: 92%